Experimental and numerical study on coupled shear walls with buckling-restrained steel plates under cyclic loading. (15th November 2019) - Li, Guo-Qiang; Li, Yan-Wen; Wang, Hai-Jiang; Pang, Meng-De; Li, Liu-Lian; Sun, Jian-Yun
Highlights: A novel system of coupled shear walls with buckling restrained steel plates (CW-BRSP) is proposed. Behavior of the CW-BRSP under cyclic loading is experimentally and numerically investigated. The axial load ratio, degree of coupling (DOC) and yield strength of steel core plates, are investigated parametrically. Abstract: This paper aims to investigate the seismic behavior of coupled shear wall with buckling restrained steel plates (CW-BRSP) under cyclic lateral loading. The quasi-static cyclic test on a 1/3-scaled CW-BRSP specimen was conducted. The response of CW-BRSP under cyclic loads, including the damage and failure modes, lateral force-displacement relationship, strength and stiffness degradation, energy dissipation, were observed as well as compared with those of the solid and coupled concrete shear walls. Yielding and plasticity of the buckling restrained steel plates developed with the increment of loading amplitude. Flexural cracks developed at the base of the wall piers. Test results indicated that the proposed CW-BRSP system has stable lateral load resisting and energy dissipation capacity. In addition, refined nonlinear finite element model of the CW-BRSP was developed and validated. Parametric study results indicated that the axial load ratio, degree of coupling and strength of buckling restrained steel plates has significant effect on seismic behavior of the CW-BRSP.